TARQIYYATU KUDRATI FAHMI TARKIB AL-LUGHAH AL-ARABIYAH BI NAMUDZAJ MAKE A MATCH - Aisyatul Hanun; Amirul Mukminin; Muhammad Syarifuddin; Mohammad Atmim Aisyi (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
The obstacle which has suffered by students when they learn Arabic languange is their lower comprehending about languange structure. This matter can be knowed from KKM Arabic languange lesson in class VII C MTs Negeri 12 Banyuwangi that setted as 75, but only 10 students of 28 students can reach KKM whereas the other 18 students can’t yet reach KKM which setted. Else that, the data of daily test result analysis has indicated that the students ability of comprehending Arabic languange structure is very low. The purpose of this study was to find out whether the Make a Match model can improve the ability to understand the structure of Arabic in class VII C MTs Negeri 12 Banyuwangi at school? In this study using classroom action research (PTK). The plan of actions was held by two cycles. Each cycle consist of 4 phase, viz planning, acting, observation, and reflecting. Data collection has been held by doing individual asessment (test) and fused with triangulation technique viz interview, observation, and documentation. Data analysis that are used is descriptive analysis technique. The result of this research is Make a Match model be able to improve ability of comprehending Arabic languange structure in class VII C MTs Negeri 12 Banyuwangi at school. That case based study completeness of student, percentage at the pre-cycle was 44% then improved at the first cycle 65,38% and at the second cycle become 80%.